3329 Hemoglobin selectively inhibits renal proximal tubular uptake of proteins: Implications for vitamin D deficiency and kidney disease in sickle cell disease. (27th March 2019) - Gliozzi, Megan L.; Rbaibi, Youssef; Vitturi, Dario A.; Tejero, Jesús; Weisz, Ora A.
Abstract : OBJECTIVES/SPECIFIC AIMS: While Hb-induced toxicity has been assumed to cause PT dysfunction, the development of tubular proteinuria from this dysfunction in SCD patients is not well understood. We previously found that free Hb, at concentrations predicted to be present chronically and during hemolytic crisis in the tubular filtrate of SCD patients, impairs uptake of albumin by PT cells via direct competition for binding to megalin and cubilin receptors. The purpose of this study is to further evaluate the consequences of increased filtered Hb concentrations on vitamin D reabsorption and activation. METHODS/STUDY POPULATION: We have developed a PT cell culture model that closely mimics in vivo PT cell structure, morphology, and endocytic capacity. Using this model, we treated cells with physiologic levels of cell-free Hb estimated in SCD and measured protein endocytosis and toxicity/oxidative stress. Endocytosis of fluorescently-tagged DBP and RBP were evaluated and quantified by confocal imaging and spectrofluorometry. Cellular toxicity and oxidative stress were assessed by measuring aconitase activity and accumulation of mitochondrial reactive oxygen species. RESULTS/ANTICIPATED RESULTS: PT cell uptake of DBP was significantly inhibited by both concentrations of Hb estimated to be filtered into the tubule lumen under chronic conditions (0.6μM Hb; 39% inhibition) and hemolytic crisis (≤20μM Hb; up to 92% inhibition) in SCD patients. ****p<0.0001 by one-way ANOVA, Dunnett's multiple comparisons test. PT cell uptake of RBP was minimally affected by the same concentrations of Hb that profoundly inhibited internalization of DBP. RBP uptake was not significantly inhibited by all concentrations of Hb tested except the estimated hemolytic crisis maximum concentration (20μM; 27% inhibition). RBP uptake inhibition at 20μM Hb treatment was dramatically less than DBP uptake inhibition under the same treatment condition (27% RBP inhibition vs 92% DBP inhibition). *p<0.05 by one-way ANOVA, Dunnett's multiple comparisons test. Mitochondrial oxidative stress, measured as a decrease in aconitase activity, was significantly increased in cells exposed to Hb ( 43% aconitase activity reduction after 72h 20μM Hb treatment, and 11% aconitase activity reduction after 72h 1μM Hb treatment). *p<0.05, **p<0.01 by one-sample t-test of the differences between treatment and untreated control conditions. We are currently assessing changes in PT cell vitamin D hydroxylase expression levels and vitamin D metabolism after exposure to chronic and hemolytic concentrations of Hb. Because oxidative stress has been previously reported to affect hydroxylase expression and activity, we expect to find a decrease in vitamin D hydroxylase expression and/or activity, resulting in decreased vitamin D activation. DISCUSSION/SIGNIFICANCE OF IMPACT: Our results suggest that competition for megalin/cubilin binding between Hb and normally-filtered proteins, including DBP, may be the primary cause of tubular proteinuria in SCD patients. This inhibition appears to be selective for proteins that are largely α-helical in structure, such as albumin and DBP. Understanding the structural basis for Hb competition with filtered proteins for PT uptake could identify biomarkers to detect tubular proteinuria in SCD patients prior to the onset of kidney disease. This may also help develop therapeutic compounds that would selectively inhibit Hb binding to megalin/cubilin receptors. We have developed a highly sensitive fluorescence-based assay to test for such compounds. Inhibition of DBP uptake and vitamin D metabolism in the PT could lead or contribute to vitamin D deficiency. To our knowledge, our study is the first to suggest a mechanism for vitamin D deficiency commonly observed in SCD patients. Ongoing studies focus on measuring vitamin D metabolism in both cell and mouse models of SCD.